A MEASUREMENT AND COMPARISON OF DIGESTIVE ENZYMES ACTIVITY IN LARVAE OF CASPIAN BROWN TROUT AND RAINBOW TROUT AT INITIATION OF EXOGENOUS FEEDING - A. Zamani; A. Hajimoradlo; R. Madani; M. Farhangi; A. Vilaki (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2008)
To determine the digestive capacity of larvae in Caspian brown trout and Rainbow trout, activity of digestive enzymes including pepsin, trypsin, chymotrypsin, a-amylase, lipase and alkaline phosphatase in 2/3 and complete yolk-sac absorption stages were assessed. Results showed enzyme activity was significantly higher in Rainbow trout than in Caspian brown trout at 2/3 yolk-sac absorbtion stage (P<0.05). Enzyme activity was increased in Caspian brown trout at complete yolk-sac absorption. The enzymes pepsin, trypsin, a-amylase, lipase and alkaline phosphatase were higher in Caspian brown trout than in Rainbow trout but of these only a-amylase was significantly different between the two (P<005). Chymotrypsin was lower in Caspian brown trout than in Rainbow trout but not significantly (P>0.05). At the start of feeding, activity of pepsin, trypsin, chymotrypsin and alkaline phosphatase were higher in Rainbow trout than in Caspian brown trout but the difference was not significant for pepsin (P>0.05) whereas trypsin, chymotrypsin and alkaline phosphatase were significant different between the two (P<0.05). A-amylase was lower in Rainbow trout than in Caspian brown trout but not significantly (P>0.05). Lipase was similar in both fish. Higher enzyme activity in Rainbow trout than in Caspian brown trout at 2/3 yolk-sac absorption shows the high ability for digesting food in rainbow at this stage. Also, low enzyme activity in Caspian brown trout at this stage is believed to be one of the reasons for low food intake and digestion at this stage.